2000
DOI: 10.1054/bjoc.2000.1513
|View full text |Cite
|
Sign up to set email alerts
|

Definition of the role of chromosome 9p21 in sporadic melanoma through genetic analysis of primary tumours and their metastases

Abstract: Summary Malignant melanoma (MM) is thought to arise by sequential accumulation of genetic alterations in normal melanocytes. Previous cytogenetic and molecular studies indicated the 9p21 as the chromosomal region involved in MM pathogenesis. In addition to the CDKN genes (p16/CDKN2A, p15/CDKN2B and p19 ARF , frequently inactivated in familial MM), widely reported data suggested the presence within this region of other melanoma susceptibility gene(s). To clearly assess the role of the 9p21 region in sporadic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 40 publications
0
20
0
2
Order By: Relevance
“…There is currently a lack of information to define the exact stage at which LOH, microstallite instability, or CDKN2A promoter methylation occurs. [28][29][30] Indeed, recent studies on somatic mutations and LOH at 9p21 suggested that somatic mutations in sporadic primary melanoma are infrequent and found LOH in thick rather than in thin primary melanomas. 31 Alternatively to LOH, a mechanism involving altered folding of the p16 protein from a mutated allele 32 may explain the mislocalized pattern as the result of impaired passage from the nucleus to cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently a lack of information to define the exact stage at which LOH, microstallite instability, or CDKN2A promoter methylation occurs. [28][29][30] Indeed, recent studies on somatic mutations and LOH at 9p21 suggested that somatic mutations in sporadic primary melanoma are infrequent and found LOH in thick rather than in thin primary melanomas. 31 Alternatively to LOH, a mechanism involving altered folding of the p16 protein from a mutated allele 32 may explain the mislocalized pattern as the result of impaired passage from the nucleus to cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…CDKN2A inactivation can result from diVerent genetic events. In 20 to 71% of primary sporadic melanomas loss of heterozygosity (LOH) was reported at one or more polymorphic microsatellite markers on 9p21 (Kumar et al 1999;Cachia et al 2000;Palmieri et al 2000). Hemi-or homozygous deletions of CDKN2A were detected in 27.5% by Southern blot analysis (Flores et al 1996) while monosomy 9 was observed in 36.5% by Xuorescent in situ hybridization (FISH) (Matsuta et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of malignant melanoma cases occur in multiplex families, with the CDKN2A locus in 9p21 accounting for susceptibility in 20-57% of all melanoma families [2]. However, remaining cases of familial melanoma do not carry mutations in CDKN2A and additional tumor suppressor genes at 9p21 and elsewhere have been proposed [3]. Large numbers of nevi are the strongest known risk factor for melanoma [4] and in many familial cases susceptibility to melanoma is associated with an excess of nevi.…”
mentioning
confidence: 99%